2017
DOI: 10.1039/c6py02026g
|View full text |Cite
|
Sign up to set email alerts
|

Multi-stimuli responsive block copolymers as a smart release platform for a polypyridyl ruthenium complex

Abstract: An efficient protocol for the preparation of poly(N,N-dimethylaminoethyl methacrylate)(PDMAEMA)-based multi-stimuli responsive block copolymers (BCPs) with poly(methyl methacrylate) (PMMA)viaanionic polymerization protocols is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
47
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

7
0

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 63 publications
0
47
0
Order By: Relevance
“…11-20 organotin compounds [20][21][22] or other metallodrugs. 10,23 . This approach has been shown to be highly effective against cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…11-20 organotin compounds [20][21][22] or other metallodrugs. 10,23 . This approach has been shown to be highly effective against cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, stimuli‐responsive block copolymers—commonly referred to as smart block copolymers—can be designed to alter conformation, solubility, or even covalent structure, as a function of external triggers. Common stimuli include temperature, pH, light, redox reagents, and electrical fields …”
Section: Introductionmentioning
confidence: 99%
“…62 As examples, selenium [63][64][65] , silver 66 , gold [67][68][69] and silicon [70][71][72][73][74] nanoparticles as well as upconverting nanoparticles [75][76][77] were successfully loaded with Ru(II) polypyridine complexes, forming a drug delivery vehicle. Further, the physical encapsulation of Ru(II) polypyridine complexes into polymeric partciles [78][79][80][81][82][83][84][85][86] , micelles [87][88][89] , dendrimers 90 or liposomes [91][92] was reported. Recent studies have also shown the conjugation of Ru(II) polypyridine complexes to carbon nanotubes [93][94][95] as well as metal-organic frameworks 96-97 as a delivery system.…”
Section: Introductionmentioning
confidence: 99%